STANDARTIZATION OF IMMUNOGENICITY OF INACTIVATED VACCINE QAZVAC AGAINST CORONAVIRUS INFECTION COVID-19 FROM AN EPIDEMIOLOGICALLY RELEVANT STRAIN - Myrzakhmetova, B.Sh.; Zhapparova , G.A.; Bissenbayeva , K.B.; Toytanova , A.S.; Tuyskanova , M.S.; Nakhanova , G.D.; Nurabayev , S.Sh.; Zhugunissov , K.D.; Kutumbetov, L.B. (Eurasian Journal of Applied Biotechnology, 2023)
This article presents the results of studies on the standardization of the immunogenicity of the domestic QazVac vaccine using different methods to recommend the available ones for use in laboratories that do not require special biological protection. The immunogenicity of the vaccine was assessed by specific antibodies to the SARS-CoV-2 virus, for the detection of which a neutralization reaction and ELISA method were used. Syrian hamsters were taken as model animals. Commercial kits produced by ID-Vet, France, JSC VECTOR-BEST, Russia, as well as experimental samples of the kit manufactured at the Research Institute of Biochemical Biochemistry were used as ELISA test systems. The results obtained showed that in Syrian hamsters vaccinated with the vaccine, from the 14th day of observation, specific virus-neutralizing antibodies to the SARS-CoV-2 virus were detected in the neutralization reaction in 100% of cases.